Uncovering the Bias and Prejudice in Reporting on Islamist and Non-Islamist Terrorist Attacks in British and US Newspapers - De Coster, Stanley (Perspectives on terrorism, 2024)
This article presents an empirical analysis that unveils systematic biases in how major US and UK print media outlets portray terrorist attacks carried out by Muslim versus non-Muslim perpetrators. Employing computational text analysis of a corpus spanning over 10,233 newspaper articles published in The New York Times, The Washington Post, USA Today, The Guardian, The Daily Mail, and The Telegraph from 2003-2018, the study reveals two key disparities. First, Muslim attacks tend to elicit more negatively valenced emotional language, which may cultivate fear and stigmatisation in Muslim communities. Second, such attacks garner greater sustained media attention over time compared to those committed by non-Muslims, which exhibit a sharper decline in coverage beyond the immediate aftermath. These differences in framing and agenda-setting illuminate how media representations can contribute to socially constructing particular forms of ideological violence as more existentially threatening. By empirically documenting biases in terrorism coverage, the article raises critical concerns about journalistic objectivity and the media’s role in perpetuating prejudicial narratives that enable policies targeting Muslims while minimising other security threats. The findings underscore the urgency of promoting more responsible reporting practices and inclusive public discourse surrounding extremism and its underlying drivers.